Length of hospital stay and factors associated with very-low-birth-weight preterm neonates surviving to discharge a cross-sectional study, 2022 - Yimenu Mehretie; Ashenafi Tazebew Amare; Geta Bayu Getnet; Birhanu abie Mekonnen (BMC, 2024)
Abstract Background The length of hospital stay of very-low-birth-weight neonates (birth weight < 1500 g) depends on multiple factors. Numerous factors have been reported to influence the length of hospital stay (LOS). The objective of this study was to identify the length of hospital stay and associated factors among very-low-birth-weight preterm neonates. Method A hospital-based, cross-sectional study was conducted. Data was collected using a pretested, structured questionnaire from April 1 to November 30, 2022. The data was entered using Epidata and Stata version 15.1. The frequencies, mean, median, and interquartile range were used to describe the study population about relevant variables. A linear regression model was used to see the effect of independent variables on dependent variables. Result About 110 very low-birth-weight preterm neonates who survived to discharge were included in the study. The median birth weight was 1370 g, with an IQR of 1250-1430. The mean gestational age was 32.30 ± 1.79 weeks. The median length of hospital stay was 24 days, with an IQR of 13.5-40. The gestational age, type of initial management given, and presence of complications had a significant association with the length of hospital stay for VLBW preterm neonates. Conclusion The median hospital stay was 24 days. The gestational age, presence of complications, and type of initial management given were associated with LOS for VLBW preterm neonates. The length of the hospital stay of the VLBW preterm neonates can be reduced by applying the standards of care of very-low-birth-weight preterm neonates.